PEMANFAATAN PEMBELAJARAN BERBASIS WORDWALL SEBAGAI INOVASI DALAM PENDIDIKAN ISLAM (Penelitian di Kelas XII SMA Asshiddiqiyah Garut) - Permana Sidik; Nurlaila Fitri; Widi Fuzi Widayanti Ikrima; Ubun Bunyamin; Lilis Fauziyah; M. Tajudin Zuhri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to examine how SMA ASSHIDIQIYAH Garut's 12th grade Islamic education students have adapted the innovative practice of using word walls for learning. In today's information age, educational pursuits need to be flexible enough to accommodate new forms of technology and data. Teachers should come up with new ways of assessing their students' progress and developing engaging learning materials. Islamic education is a required subject in SMA ASSHIDIQIYAH Garut, thus instructors have a responsibility to make class interesting and fun for their pupils. Using a qualitative methodology and a case study design, the research demonstrated that students like using the educational game Wordwall during quizzes and practice sessions. Students' engagement with Islamic education material was greatly enhanced using Wordwall, which helped to alleviate their boredom with the subject. Interviews with Mrs. Eka Kurniati, S.Pd., the VP of student affairs, and PAI instructor Nurlaila Fitri were part of the data collection process, as was classroom observation. Students' cognitive abilities, knowledge of Islamic principles, and social skills in teamwork and communication are all improved when Wordwall-based learning is integrated as an innovation in Islamic education, according to the results. Time restrictions, lack of teacher preparation, and inadequate learning materials are some of the obstacles to adopting Wordwall-based learning. To maximize the use of Wordwall in Islamic education, schools should provide instructors thorough training and make sure there are more complementary learning tools.